Induction of Inflammation and Fibrosis by Semaphorin 4A in Systemic Sclerosis. Issue 10 (27th August 2019) - Carvalheiro, Tiago; Affandi, Alsya J.; Malvar‐Fernández, Beatriz; Dullemond, Ilse; Cossu, Marta; Ottria, Andrea; Mertens, Jorre S.; Giovannone, Barbara; Bonte‐Mineur, Femke; Kok, Marc R.; Marut, Wioleta; Reedquist, Kris A.; et al.
Abstract : Objective: To analyze the potential role of semaphorin 4A (Sema4A) in inflammatory and fibrotic processes involved in the pathology of systemic sclerosis (SSc). Methods: Sema4A levels in the plasma of healthy controls (n = 11) and SSc patients (n = 20) were determined by enzyme‐linked immunosorbent assay (ELISA). The expression of Sema4A and its receptors in monocytes and CD4+ T cells from healthy controls and SSc patients (n = 6–7 per group) was determined by ELISA and flow cytometry. Th17 cytokine production by CD4+ T cells (n = 5–7) was analyzed by ELISA and flow cytometry. The production of inflammatory mediators and extracellular matrix (ECM) components by dermal fibroblast cells (n = 6) was analyzed by quantitative polymerase chain reaction, ELISA, Western blotting, confocal microscopy, and ECM deposition assay. Results: Plasma levels of Sema4A, and Sema4A expression by circulating monocytes and CD4+ T cells, were significantly higher in SSc patients than in healthy controls ( P < 0.05). Inflammatory mediators significantly up‐regulated the secretion of Sema4A by monocytes and CD4+ T cells from SSc patients ( P < 0.05 versus unstimulated SSc cells). Functional assays showed that Sema4A significantly enhanced the expression of Th17 cytokines induced by CD3/CD28 in total CD4+ T cells as well in different CD4+ T cell subsets ( P < 0.05 versus unstimulated SSc cells). Finally, Sema4A induced a profibrotic phenotype in dermal fibroblasts from both healthy controls and SSc patients, which was abrogated by blocking or silencing the expression of Sema4A receptors. Conclusion: Our findings indicate that Sema4A plays direct and dual roles in promoting inflammation and fibrosis, 2 main features of SSc, suggesting that Sema4A might be a novel therapeutic target in SSc.